Personal Determinants of Functioning in the Teaching Profession - Poraj, Grażyna (Nauczyciel wczesnej edukacji wobec zmian społeczno-kulturowych, 2016)
Numerous publications on organizational psychology have shown that there is a direct relationship between individual characteristics of people and the development of their career. The study was aimed at searching for a relationship between personality traits and job adaptation in teachers. There were examined 390 teachers from all education levels. The following tools were used: NEO-FFI to characterize personalities, MBI to measure burnt-out symptoms, and AOB to describe levels of work satisfaction. The obtained results have allowed for distinguishing three groups of teachers (passionate teachers, artisan teachers, and frustrated teachers) with distinct personality profiles and work satisfaction, and different symptoms of burnt-out in their work with students. Only one group, passionate teachers, has presented a high level of job adaptation. It is directly related to personal characteristics of the examined teachers.